Primitivism and modern art - Rhodes, Colin; Thames and Hudson (New York : Thames and Hudson, 1994)
A fascination with the "primitive" lies at the heart of some of the most influential developments in Western art produced between 1890 and 1950 - a time that witnessed both the "heroic" period of modern art and the apogee and decline of the West's colonial power. Many groups have a times been labeled as primitive, including the so-called tribal peoples from Africa, Oceania and North America, but also prehistoric cultures, European peasants, the insane and children. Through the lens of their own society, many modern artists looked both to the art and to the world-view of the primitive as a means of challenging established beliefs, but the primitive to which they turned was as varied as the movements in modern art of which they were a part. Colin Rhodes breaks new ground, drawing on a wide and diverse range of material, from high art to popular entertainment, from Darwin to Freud; the critical overview he presents supersedes all previous studies on the subject.
-- Ch. 1. The Primitive and Primitivism -- Ch. 2. Primitives Within -- Ch. 3. Savage Exoticism -- Ch. 4. Stylistic Primitivism -- Ch. 5. In Search of the Primordial -- Epilogue: Primitivism and the Dilemma of Post-Colonialism.
Includes bibliographical references (pages 203-206) and index.
Keywords: Primitivism in art; Art, Modern -- 19th century; Art, Modern -- 20th century